Macromol. Chem. Phys. 17/2014. Issue 17 (September 2014) - Chang, Won Suk; Kim, Jung Hyun; Kim, Daeho; Cho, Sung Ho; Kwon Seol, Seung
<x xml:space="preserve">Abstract</x> Front Cover: Freestanding PEDOT:PSS microwires with arched features are fabricated using fountain‐pen lithography. A gas sensor assembled with the arched wires exhibits a linear response to the concentrations of different vapor gases at room temperature. The signal to noise ratio (SNR) in the sensing response is affected by the wire diameter and the number of wires. Further details can be found in the article by W. S. Chang, J. H. Kim, D. Kim, S. H. Cho, and S. K. Seol* on page 1633. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>